Targeting positive regulatory domain I-binding factor 1 and X box-binding protein 1 transcription factors by multiple myeloma-reactive CTL - Lotz, Carina; Mutallib, Sarah Abdel; Oehlrich, Nicole; Liewer, Ulrike; Ferreira, Edite Antunes; Moos, Marion; Hundemer, Michael; Schneider, Sandra; Strand, Susanne; Huber, Christoph; Goldschmidt, Hartmut; Theobald, Matthias (The journal of immunology, 2005)
Growing evidence indicates that multiple myeloma (MM) and other malignancies are susceptible to CTL-based immune interventions. We studied whether transcription factors inherently involved in the terminal differentiation of mature B lymphocytes into malignant and nonmalignant plasma cells provide MM-associated CTL epitopes. HLA-A*0201 (A2.1) transgenic mice were used to identify A2.1-presented peptide Ag derived from the plasma cell-associated transcriptional regulators, positive regulatory domain I-binding factor 1 (PRDI-BF1) and X box-binding protein 1 (XBP-1). A2.1-restricted CTL specific for PRDI-BF1 and XBP-1 epitopes efficiently killed a variety of MM targets. PRDI-BF1- and XBP-1-reactive CTL were able to recognize primary MM cells from A2.1+ patients. Consistent with the expression pattern of both transcription factors beyond malignant and nonmalignant plasma cells, PRDI-BF1- and XBP-1-specific CTL activity was not entirely limited to MM targets, but was also associated with lysis of certain other malignancies and, in defined instances, with low-to-intermediate level recognition of a few types of normal cells. Our results also indicate that the A2.1-restricted, PRDI-BF1- and XBP-1-specific human CD8+ T cell repertoire is affected by partial self tolerance and may thus require the transfer of high-affinity TCR to break tolerance. We conclude that transcription factors governing terminal cellular differentiation may provide MM- and tumor-associated CTL epitopes.